Work, consumption and the self in the UK retail book trade - Wright, David (2004)
This thesis uses the empirical setting of the UK retail book trade to critically assess sociological accounts of work and consumption and their relationship to the self. Drawing on talk with bookshop workers, representations of the book-trade and trade press, it examines the ways in which the book-trade is historically constructed, both as a market for symbolic goods and as a distinctive type of workplace. This distinctiveness is put to use by both firms and workers in the organisation of production and in the construction of occupational identities. Its roots, though, are in the historical construction of the idea of self, drawn from romanticism, and a view of culture as related to notions of self-development. A key element of the romantic self (Campbell 1983, 1987) is its critical distance from the market and from processes of commodity exchance. As such, the creation and distribution of cultural material is rhetorically removed from broader processes of production and consumption. In the context of the book trade this generates tensions between cultural and commercial imperatives which feed into employment relationships. Books and reading are also examined as particular types of objects and activity that have been discursively associated with the development of self. These associations allow for particular orientations to work in the retain book industry which problematise accounts of the self as diminished or colonised in the context of the retail or service environment. Whilst accounts of the contemporary workplace emphasise the extent to which the 'selves' of workers are shaped by managerial initiatives, the example of the retail book trade suggests that worker conceptions of the self allow for critical distance from aspects of the employment relationship and for the aesthetic appreciation of work experiences. Rather than exemplifying the reflexive self of late-modernity, this thesis argues that this bookselling self is also embedded in relationships of cultural capital (Bourdieu 1984, 1996).